Development and validation of a spectrophotometric method for the quantification of kojic acid - GOMARA, FL; CORRER, CJ; SATO, MEO; PONTAROLO, R (Ars Pharmaceutica (Internet), 2004)
Objectives. A method for the quantification of kojic acid in bulk substances and preparations was developed andvalidated through ultraviolet spectrophotometry.Material and methods. Standardized solutions of kojic acid were used, from which the parameters of sensitivity, robustness,exactness, precision and specificity of the method were evaluated.Results and conclusions. The results obtained showed that this approach presents a linearity of between 5 and 25 μg/ml, a high degree of sensitivity, robustness - evaluated in terms of variations in the times and temperatures at whichreadings were taken -(but not in pH>7 variations), as well as exactness and precision. However, the presence of anyother substance that is absorbed within the same wavelength as kojic acid (for instance: methylparaben), can interferewith the specificity of the method, generating errors in the results obtained.